2020
DOI: 10.3389/fonc.2020.01421
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Differentially Expressed Long Non-coding RNAs and the Associated TF-mRNA Network in Tongue Squamous Cell Carcinoma

Abstract: Accumulating evidence indicates that long non-coding RNAs (lncRNAs) play crucial roles in tongue squamous cell carcinoma (TSCC) tumorigenesis. However, the comprehensive regulation of lncRNAs-transcription factors (TFs)-messenger RNAs (mRNAs) in TSCC remains largely unknown. The purpose of this study was to identify aberrantly expressed lncRNAs and the associated TF-mRNA network in TSCC. To explore lncRNA and mRNA expression profiles and their biological functions in TSCC, we surveyed the lncRNA and mRNA expre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 38 publications
0
8
0
Order By: Relevance
“…In addition, single-cell RNA sequencing (scRNA-seq), a high-resolution technology, could provide new insights into tumour evolution and has been successfully used to reconstruct clonal evolutionary trajectories during chemotherapy in breast cancer 12 . scRNA-seq could also be used to dissect the intratumour heterogeneity (ITH) of primary and metastatic tumour ecosystems in NPC 13 and draw a map of the immune phenotype in NPC [14][15][16][17][18][19][20][21][22] . Studies that focuses on the evolutionary route of metastasis in NPC are still lacking.…”
mentioning
confidence: 99%
“…In addition, single-cell RNA sequencing (scRNA-seq), a high-resolution technology, could provide new insights into tumour evolution and has been successfully used to reconstruct clonal evolutionary trajectories during chemotherapy in breast cancer 12 . scRNA-seq could also be used to dissect the intratumour heterogeneity (ITH) of primary and metastatic tumour ecosystems in NPC 13 and draw a map of the immune phenotype in NPC [14][15][16][17][18][19][20][21][22] . Studies that focuses on the evolutionary route of metastasis in NPC are still lacking.…”
mentioning
confidence: 99%
“…Previously, we screened for differentially expressed lncRNAs by analyzing six pairs of TSCC and healthy adjacent normal tissues through high-throughput RNA sequencing (Kangchen BioTech Co., Ltd.) ( 24 ) and identified the significantly overexpressed lncRNA lncKRT16P6. RT-qPCR was applied to detect the expression of differentially expressed lncRNAs.…”
Section: Resultsmentioning
confidence: 99%
“…Thus, further insight into lncRNA-dependent gene-regulatory mechanisms will provide predictive biomarkers and individual treatments for TSCC. The present study, based on our previous research results (24), performed an in-depth analysis of lncRNA expression profiles and identified a novel lncRNA, keratin 16 pseudogene 6 (lncKRT16P6), which was upregulated in TSCC tissues and cell lines and associated with TSCC tumor stage and differentiation grade. The aim of the present study was to explore the specific regulatory mechanism by which lncKRT16P6 promoted the occurrence and development of TSCC.…”
Section: Introductionmentioning
confidence: 99%
“…Long intergenic non-protein-coding RNA 511 (LINC00511) is up-regulated in different malignancies including also HNSCC [99]. This molecule has a variety of functions, including regulation of the developmental process, apoptosis, programmed cell death, focal adhesion through hemostasis, and different carcinogenic pathways [100].…”
Section: Known Lincrna Biomarkers In Hnsccmentioning
confidence: 99%